Implementasi Care Governance dalam Administrasi Publik: Studi Eksploratif Peran Aktor Non-Manusia pada Kebijakan Lingkungan Daerah - Riko Apriliano; Caesar Jourdy Permana Tauhid; Arik Prayoga (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the implementation of care governance in environmental public administration by highlighting the role of non-human actors. Based on Actor–Network Theory (ANT), exploratory qualitative research was conducted in the densely populated area of Tanjungpinang (April–June 2025). In environmental management, success is determined not only by technical skills, but also by the capacity of citizens to manage digital documents, spatial data, and technological infrastructure. Through interviews, observations, and document analysis. This approach was chosen because it allows for in-depth exploration of complex, contextual, and previously unstudied social phenomena, especially in the context of care governance to involve the relationship between humans and non-human objects in the local government ecosystem. Findings show that flood sensors, digital SOPs, inter-agency WhatsApp groups, and monitoring dashboards function as actors that trigger, direct, and accelerate coordination and decision-making. The integration of sensors and dashboards automates early warnings and the distribution of instructions, enabling rapid response. Implications: digital systems need to be designed as administrative actors with ethics, accountability, and capacity building. This study concludes that the implementation of care governance in environmental public administration at the local level cannot be separated from the active role of non-human actors such as flood sensors, digital documents, and online communication systems. Findings show that entities Findings show that these entities function not only as technical tools, but also as an integral part of a decision-making network capable of directing, accelerating, and streamlining administrative responses to environmental situations.